The Strategies of Inter-Ethnic Adaptation of Estonian Russians - Kruusvall, Jüri; Vetik, Raivo; Berry, John W. (Studies of Transition States and Societies, 2009)
Based on the inter-cultural relations model of John Berry, four diﬀerent groups among Russian-speakers in Estonia were diﬀerentiated in the analysis of ‘Integration monitoring 2005’. The analysis reveals that both similarities and diﬀerences exist between the characteristics of these four groups and the groups in the typology of Berry (integration, assimilation, marginalisation, separation). The diﬀerences that emerged are related to the assimilation and integration strategies, which proved to be rather restrained for Russian-speakers in the current social and political context in Estonia. The analysis gives us ground to claim that the strong ethnic connotation of the current nation-state model in Estonia hinders ﬁnding a positive place in this country even for those Russian-speakers, who, in fact, would like to integrate.